Power Saving for Extending Lifetime of IoT Application - Teh, Christopher Jun Qian (2018)
In this study, powers saving schemes are introduced to an IoT application which use batteries act as a power supply. Currently, there is no IoT application that implement power saving schemes in their system and the purpose of having power saving schemes is to reduce the power consumption from its connected electronic components like microcontroller, wireless module and environment monitoring sensor during the idling state of the application so that the battery lifetime can be extended for a longer period of time.